1998
DOI: 10.1046/j.1432-1327.1998.2560310.x
|View full text |Cite
|
Sign up to set email alerts
|

Probing the inhibitor‐binding site of aldose reductase with site‐directed mutagenesis

Abstract: Aldose reductase (AR) has been implicated in the etiology of the secondary complications of diabetes, and enzyme inhibitors have been proposed as therapeutic agents. While effectively preventing the development of diabetic complications in animals, results from clinical studies of AR inhibitors have been disappointing, possibly due to poor potency in man. To assist in the design of more potent and specific inhibitors, crystallographic studies have attempted to identify enzyme-inhibitor interactions. Resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…30,33 Replacing the hydrophobic residues Trp 22 and Trp 114 with Ala decreased the potential for nonbonded interactions. Except in the case of the binding of tolrestat to the Trp 114 to Ala mutant, the mutations resulted in 400-to 2,200-fold increases in IC 50 values, suggesting that hydrophobic interactions between the enzyme and inhibitor in solution contribute to the inhibitor's binding stability in the active site.…”
Section: Results and Discussion X-ray Crystallography And Molecular Mmentioning
confidence: 99%
See 2 more Smart Citations
“…30,33 Replacing the hydrophobic residues Trp 22 and Trp 114 with Ala decreased the potential for nonbonded interactions. Except in the case of the binding of tolrestat to the Trp 114 to Ala mutant, the mutations resulted in 400-to 2,200-fold increases in IC 50 values, suggesting that hydrophobic interactions between the enzyme and inhibitor in solution contribute to the inhibitor's binding stability in the active site.…”
Section: Results and Discussion X-ray Crystallography And Molecular Mmentioning
confidence: 99%
“…ALR1 activity was assayed spectrometrically in a Shimadzu UV-160A spectrophotometer by following the decrease in absorption of NADPH at 340 nm with dl-glyceraldehyde as substrate and according to published methodology. 30 For IC 50 measurements, the substrate concentration was maintained at 5 mM and a 1% DMSO was used with or without different concentrations of inhibitors. The temperature was maintained at 25°C and measurements were carried out in duplicates or triplicates with typical variations of less than 5%.…”
Section: Purification Of Alr1mentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, the nature of inhibition by the glutathione analogs was uncompetitive versus the aldehyde substrate. Although for a simple, one-substrate/one-product reaction scheme, this would suggest that the inhibitors bind to the E⅐S complex, previous experiments have shown that several AR inhibitors such as sorbinil, tolrestat, and zopolrestat that do not display competitive inhibition (26,27) bind exclusively to the active site of the enzyme (27)(28)(29)(30). This is because the rate-limiting step in AR catalysis is the slow isomerization of the E⅐NADP binary complex (31).…”
Section: Since These Values Correspond To [M ϩ H]mentioning
confidence: 99%
“…This pocket was shown to be closed in the ALR2-sorbinil complex but opened in the ALR2-tolrestat complex, which allowed tolrestat to bind within this pocket, albeit in a different conformation to the ALR2-zopolrestat structure [34]. The W111A mutant decreased the inhibition by 400-fold for zopolrestat but the W111Y mutant had no effect, which suggested that the effects of the Ala mutation were due to changes in the van der Waals interactions of the ALR2-ARI complex [37]. The most significant change in activity was observed for the W20A mutant, even though the number of eliminated van der Waals contacts was less than that for the W111A mutation.…”
Section: Identification Of the Residues Involved In The Enzymatic Mecmentioning
confidence: 99%